Analisis Prediksi Kebangkrutan Menggunakan Metode Altman (Z-Score) Pada Perusahaan Farmasi (Studi Kasus Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2011 â 2015) - wulandari, fitria; Burhanudin, Burhanudin; Widayanti, Rochmi (Universitas Muhammadiyah Surakarta, 2017)
This study aimed to analyze the condition of the company using the Altman Z-Score to predict the potential bankruptcy of the five pharmaceutical companies listed on the Indonesia Stock Exchange in 2011 to 2015. The sampling methodÂ is using purposive sampling with a sample of five pharmaceutical companies. This research is descriptive with quantitative approach. The results showed that: (1)Â in 2011 to 2015 the five pharmaceutical companies are in the good category, the number ofÂ Z-Score from all companies are Â â¥ 2.99. (2) MoreoverÂ from the five pharmaceutical companies that were analyzed PT Merck Tbk in 2011, 2013 and 2014 had the highest number for Z-Score at 8.45, 6.3 and 5.92. (3) PT Kalbe Farma Tbk in 2012 and 2014 had the highest number for Z Score at 6.08 and 5.91. The results of this study are expected for pharmaceutical companies to maintain liquidity to meet all its obligations so that will interestÂ Â investors and creditors. Companies are expectedÂ to manage assets to increase sales and generate profits.Â